Potential implications of rising sea level on American Horseshoe Crab (Limulus polyphemus) spawning beaches in two Florida counties - Danielle Contrada; Claire Crowley-McIntyre; Berlynna Heres (PLoS ONE, 2025)
Coastlines support a diversity of wildlife and are used as spawning sites for many species. Though, as sea levels rise, many coastlines will be inundated, affecting species that live or nest in these habitats. The American Horseshoe Crab ( Limulus polyphemus ) requires specific environmental conditions for optimal egg development in coastal habitats. This study used reports of horseshoe crab sightings in two Florida counties to identify characteristics associated with their spawning habitats. A 0.6-meter-wide shoreline polygon was created in ArcGIS Pro and each habitat type within the polygon was identified. Using sea-level rise scenarios for 2040, 2070, and 2100, the percentage of habitat loss within these spawning polygons was predicted. In Pinellas County, spawning was predominantly associated with sheltered tidal flats and mangroves. In Brevard County, spawning was most often associated with fine- to medium-grain sand beaches and mangroves. These results demonstrated that each sea-level rise scenario projects a change in habitat area within the shoreline polygons, most notably in the 2040 projection. By 2100 in Pinellas County, 96.3% of mangroves and 87.4% of sheltered tidal flats within the shoreline polygons were predicted to be lost or changed to a different habitat type. In Brevard County by 2100, 98% of fine- to medium-grain sand beaches and 94.8% of mangroves within the shoreline polygons were predicted to be lost or changed to a different habitat type.